Thermal interquark potentials for bottomonium using NRQCD from the HAL QCD method - THOMAS SPRIGGS (Proceedings of The 38th International Symposium on Lattice Field Theory — PoS(LATTICE2021), 2022)
We report progress results from our calculation of the interquark potential of bottomonium at non-zero temperature using the HAL QCD method. We use NRQCD correlation functions of non-localmesonic -wave states to obtain the central potential as a function of temperature. These resultshave been obtained using our anisotropic 2+1 flavour "Generation 2" FASTSUM ensembles.